PTK-Based Scientific Writing Training for High School Mathematics Teachers in South Central Timor Regency: Pelatihan Penulisan Karya Tulis Ilmiah Berbasis PTK bagi Guru Matematika SMA Di Kabupaten Timor Tengah Selatan - Suban Garak, Siprianus; Damianus Dao Samo; Imelda Hendriani Eku Rimo (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this PKM activity is to help high school mathematics teachers in South Central Timor (TTS) to create PTK-based written work and be able to publish it. Meanwhile, the background for holding this PKM is because the majority of high school mathematics teachers have difficulty getting promoted because they are hampered by published scientific papers.The specific target to be achieved through PKM activities for the community (teachers) is to improve teachers' skills and abilities in creating and publishing PTK-based written work.The methods used in this activity are lecture, discussion, question and answer, demonstration, and practice. Providing material I, namely what is PTK, characteristics of PTK, systematics of written work based on PTK and how to make a good PTK. The second material is about the implementation of PTK writing which is stated through filling in a reflection form to find PTK problems. Next is the final material regarding the publication of Scientific Works. This activity went well and received a positive response from the activity participants